Order-Aware Twigs: Adding Order Semantics to Twigs - M., Abdul Nizar; Puligundla, Sreenivasa Kumar (Journal of Information and Data Management, 2012)
Although many algorithms have been proposed for evaluating XPath queries containing child and descendantaxes and predicates XPATH (/,//,[ ]) against XML data, there are very few efforts towards eveloping algorithms for processing path expressions with other axes namely, following, preceding, following-sibling and preceding-sibling. In this paper, we demonstrate that the conventional twig-structure, which is used to represent expressions in the subset XPATH (/,//,[ ]) has no order information built into it and hence fails to model XPath expressions with ordered axes. This motivates us to introduce a new type of twig-structure, which we call Order-aware Twig, to effectively represent XPath expressions with ordered axes.